2009
DOI: 10.2174/138161209787582093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metabolic Approach in Diabetic Patients with Coronary Artery Disease

Abstract: The pivotal therapeutic role of myocardial metabolic modulation in ischemic heart disease (IHD) is increasingly recognized. Among the others, inhibitors of free fatty acids (FFA) oxidation have been consistently shown to play an important role in the therapeutic strategy of IHD patients. Additionally, abnormalities of glucose homeostasis are consistently present in patients with IHD, definitely contributing to the progression of the primary disease. If not adequately treated, in most patients glucose metabolis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
6
0
3
Order By: Relevance
“…In type 2 diabetic humans and in obese rodents, oral administration of CPT-1 inhibitors such as etomoxir and oxfenicine consistently elevates glucose oxidation and ameliorates hyperglycemia and hyperinsulinemia (Barnett et al, 1992; Deems et al, 1998; Dobbins et al, 2001; Fragasso et al, 2009; Hubinger et al, 1997). However, when insulin sensitivity was assessed by the euglycemic clamp technique, some studies reported improvements after etomoxir treatment whereas others found the opposite effect (Dobbins et al, 2001; Hubinger et al, 1997).…”
Section: Fueling the Furnace: Accelerating Versus Overloading β-Oxidamentioning
confidence: 99%
“…In type 2 diabetic humans and in obese rodents, oral administration of CPT-1 inhibitors such as etomoxir and oxfenicine consistently elevates glucose oxidation and ameliorates hyperglycemia and hyperinsulinemia (Barnett et al, 1992; Deems et al, 1998; Dobbins et al, 2001; Fragasso et al, 2009; Hubinger et al, 1997). However, when insulin sensitivity was assessed by the euglycemic clamp technique, some studies reported improvements after etomoxir treatment whereas others found the opposite effect (Dobbins et al, 2001; Hubinger et al, 1997).…”
Section: Fueling the Furnace: Accelerating Versus Overloading β-Oxidamentioning
confidence: 99%
“…causam alterações no metabolismo do endotélio vascular, levando a aterogênese acelerada, alteração cardiovascular prematura, além de contribuir para o desenvolvimento de doença cardiovascular em pacientes diabéticos (Fragasso et al, 2009).…”
Section: Conclusãounclassified
“…Os efeitos benéficos combinados da inibição parcial de AGL e metabolismo da glicose tornam o uso de fármacos com esse princípio particularmente atraente, especialmente nos pacientes cardiopatas que apresentam anormalidades do miocárdio e do metabolismo da glicose (Fragasso et al, 2009). Por meio de uma revisão sistemática da literatura, avaliaram-se a eficácia e segurança do uso da TMZ combinada à terapia convencional no tratamento da angina estável em pacientes diabéticos não respondedores a betabloqueadores, nitratos e bloqueadores dos canais de cálcio, quando comparada ao padrão de tratamento adotado pelo SUS.…”
Section: Conclusãounclassified
“…As the rate of glycolysis decreases, production of lactate and H + increases that leads to intracellular acidosis. Under this condition, reduced activity of Na + / K + ATPase and Na + -Ca 2+ exchanger result sodium and calcium overload and may enhance myocyte damage [4]. It is important to find some new treatments that partially inhibit extensive fatty acid ß-oxidation and promote glucose consumption in diabetic heart.…”
Section: Introductionmentioning
confidence: 99%